If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(20h + -18) + -20h = 3(-1h + -7) Reorder the terms: -2(-18 + 20h) + -20h = 3(-1h + -7) (-18 * -2 + 20h * -2) + -20h = 3(-1h + -7) (36 + -40h) + -20h = 3(-1h + -7) Combine like terms: -40h + -20h = -60h 36 + -60h = 3(-1h + -7) Reorder the terms: 36 + -60h = 3(-7 + -1h) 36 + -60h = (-7 * 3 + -1h * 3) 36 + -60h = (-21 + -3h) Solving 36 + -60h = -21 + -3h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '3h' to each side of the equation. 36 + -60h + 3h = -21 + -3h + 3h Combine like terms: -60h + 3h = -57h 36 + -57h = -21 + -3h + 3h Combine like terms: -3h + 3h = 0 36 + -57h = -21 + 0 36 + -57h = -21 Add '-36' to each side of the equation. 36 + -36 + -57h = -21 + -36 Combine like terms: 36 + -36 = 0 0 + -57h = -21 + -36 -57h = -21 + -36 Combine like terms: -21 + -36 = -57 -57h = -57 Divide each side by '-57'. h = 1 Simplifying h = 1
| g=(x+7)(x+3) | | -12r+6(-16r-5)=-6(19r+19) | | 2(3x+4)=3(6x-5) | | 9+7j=4j | | X+5-2x=3+x | | x=2000000+0.333y | | 2x-24=82 | | -7-3n=-5n | | -7-2r=4+9r | | 2+4*5=30 | | -8=-3n+5n | | -6(-m-8)=-10m | | (2x-1)/3=(5x-6)/4 | | -10-7q=10-9q | | 11n-9=5n+45 | | 3(2r+14)=2(25+4) | | -9-9(13t-1)=6(-20t-10) | | 5n+22=22 | | 3(f-2)=7(f+2) | | C+5-2x=3+x | | -4y+b= | | 4(x+5)=-4x-20 | | 12n+22=5 | | 18d+18+20=2(15d-17) | | 5(x+1)-6x=-11x | | f(p)=p^2-6p+1 | | y=3500x+31500 | | y-14=y | | 2.8v-3.54-17.4v=-9.19-15.1v | | 12n+22=44 | | (x-3/2)^2-5/4=0 | | 10-5s=-10-3s |